Resilience, stress and injuries in the context of the Brazilian elite rhythmic gymnastics - Codonhato, R.; Rubio, V.; Pereira Oliveira, P. M.; Ferezin Resende, C.; Akawana Martins Rosa, B.; Pujals, C.; Fiorese, L. (PLOS ONE, 2018)
The study had the goal to study the relationship between resilience, stress and injuries in the sport context. Eight female athletes, part of the Rhythmic Gymnastics Brazilian Team along the Olympic Cycle 2015-2016 participated in the study, with a mean age of 20.4±2.5 years. The following instruments were used: RESTQ-76 Sport, CD-RISC 10, documental analysis of physical therapy records, and structured questionnaire. Data was analyzed by descriptive statistics (frequency, mean and standard deviation); Repeated Measured ANOVA with Bonferroni`s post-hoc, Student`s "t" test, Friedman test, Pearson Correlation Coefficient, Cohen`s d, and inductive thematic analysis. We found relatively stable levels of stress and recovery across the season; total recovery levels were higher than stress at all four measured timepoints (p<0.05); All athletes had at least one injury, with a total of 14 injuries; No significant correlations were found between the quantitative scores of resilience, stress and recovery; Training and the sport`s scoring system were the most relevant perceived stressors; athletes presented meta-cognition and a non-positive evaluation (neutral) of stressors; Social support was considered the main psychological factor for the resilience process; such process resulted in improved control and interpretation of emotions; Our hypothesized model proposes that, in the relationship between stress and injuries, resilience acts by optimizing the injury recovery process. It was concluded that resilience plays a role in the process of injury rehabilitation and stress control in elite rhythmic gymnastics` athletes.